Automated patterns of head dynamics are associated with psychopathic traits in incarcerated women. (January 2023) - Rodriguez, Samantha N.; Gullapalli, Aparna R.; Tirrell, Palmer S.; Maurer, J. Michael; Egala, Ugesh; Edwards, Bethany G.; Anderson, Nathaniel E.; Harenski, Carla L.; Decety, Jean; Neumann, Craig S.; Kiehl, Kent A.
Abstract: Men with elevated psychopathic traits have been characterized by unique patterns of nonverbal communication, including more fixed and focused head positions during clinical interviews, compared to men scoring low on measures of psychopathy. However, it is unclear whether similar patterns of head dynamics help characterize women scoring high on psychopathic traits. Here, we utilized an automated detection algorithm to assess head position and dynamics during a videotaped clinical interview (i.e., the Psychopathy Checklist – Revised [PCL-R]) in a sample of n = 213 incarcerated women. PCL-R Total, Factor 1 (i.e., interpersonal and affective psychopathic traits), and Factor 2 (i.e., lifestyle/behavioral and antisocial/developmental psychopathic traits) scores were associated with a pattern of head dynamics indicative of a rigid head position. The current study extends analyses of nonverbal behavior studies in men to women and highlights how individuals with elevated psychopathic traits demonstrate unique nonverbal behaviors relative to individuals who score low on psychopathic traits. The implications and clinical value of these findings are discussed. Highlights: Psychopathy is associated with unique patterns of nonverbal communication. An automated detection algorithm was created to study nonverbal behavior in women. PCL-R interviews were recorded to measure head dynamics throughout the interview. Psychopathy scores were associated with more time spent in minimal movement ranges. Our results improve our understanding of the manifestation of psychopathy in women.